2018
DOI: 10.1186/s12879-018-3430-0
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour and delayed management of tuberculosis patients in rural Bangladesh

Abstract: BackgroundEarly diagnosis of tuberculosis (TB) and involvement of the public-private partnership are critical to eradicate TB. Patients need to receive proper treatment through the National Tuberculosis Control Programme (NTP). This study describes various predictors for health seeking behaviour of TB patients and health system delay made by the different health care providers.MethodsA cross-sectional study was conducted in a public health facility of a rural area in Bangladesh. Newly diagnosed smear positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 24 publications
1
28
3
1
Order By: Relevance
“…This paper aimed to describe the health-seeking behavior of discharged patients with COVID-19 infection, with consideration of variables including how much times patients sought treatment, when and where the first sought treatment, disease course and factors affecting health-seeking behavior. Different from other similar studies about health-seeking behavior of patients with respiratory infectious disease [13][14][15], there were no significant difference between gender, age, and symptoms on health-seeking behaviors of patients with COVID-19. This maybe for a new Public Health Emergency of International Concern, the health-seeking behavior of patients with COVID-19 mainly depends on government policies at early stage of the outbreak.…”
Section: Discussioncontrasting
confidence: 99%
“…This paper aimed to describe the health-seeking behavior of discharged patients with COVID-19 infection, with consideration of variables including how much times patients sought treatment, when and where the first sought treatment, disease course and factors affecting health-seeking behavior. Different from other similar studies about health-seeking behavior of patients with respiratory infectious disease [13][14][15], there were no significant difference between gender, age, and symptoms on health-seeking behaviors of patients with COVID-19. This maybe for a new Public Health Emergency of International Concern, the health-seeking behavior of patients with COVID-19 mainly depends on government policies at early stage of the outbreak.…”
Section: Discussioncontrasting
confidence: 99%
“…Encouragingly for patients, prices of essential antibiotics in private pharmacies in Bangladesh, including model stores, were not much higher than international prices in a recent study by , with only limited price increases between 2003 and 2019 44 . The increase in cases with dengue 21 , and the continued challenges with tuberculosis in Bangladesh, with patients typically seeking help from non-qualified practitioners before seeking help from qualified professionals, also needs addressing [45][46][47][48] . Encouragingly, whilst there are still cases of malaria in Bangladesh, co-ordinated activities have reduced these by more than 50% in 2016 versus 2010 49 .…”
mentioning
confidence: 99%
“…[10][11][12][13] Studies have reported the involvement of non-qualified and alternative caregivers in the management of chronic diseases especially in rural areas and resource-poor countries. [14][15][16][17][18] Similar patterns have been observed in the care of patients with SCD. 17,[19][20][21] These observations reflect that many people in Nigeria and other developing countries have strong beliefs in religious institutions and non-orthodox care centres for healing and healthcare services as people in these communities sometimes refer to children suffering from chronic medical conditions like SCD as being afflicted by spirits/devils because of the nature and clinical presentation of these diseases and as such, believe that these children need spiritual and other non-orthodox care.…”
Section: Introductionmentioning
confidence: 73%